The Transformation of European Fretted Zithers in the 19th and 20th Centuries - Posta, Máté (Ethnographica et Folkloristica Carpathica, 2024)
Different types of fretted zithers appeared in the western and northern parts of Europe and in the Alpine regions 500-600 years ago to meet the needs of rural folk music. In the 19th and 20th centuries, in northern Germany, the Czech Republic, Denmark, Sweden and the Netherlands, zithers were constantly pushed out of village folk music. The final blow was the spread of the accordion to the zither. However, in some regions of southern Germany, Bavaria and Austria, zithers did not disappear, but underwent a number of significant modifications. In the first step, the volume of the instrument was increased (Salzburg form). This variety, called the Kratzzither was further developed in two different ways. To ensure that the zither could play with other instruments, the Scherrzither and Raffele were developed. Another development direction of the Kratzzither was the Schlagzither, which already provided a harmonic accompaniment to the melody. The systematic development of the Schlagzither made possible the birth of the Austrian and German Konzertzithers, whose harmonization already meets the requirements of classical music.